OMI Satellite and Ground‐Based Pandora Observations and Their Application to Surface NO2 Estimations at Terrestrial and Marine Sites. Issue 2 (29th January 2018) - Kollonige, Debra E.; Thompson, Anne M.; Josipovic, Miroslav; Tzortziou, Maria; Beukes, Johan P.; Burger, Roelof; Martins, Douglas K.; van Zyl, Pieter G.; Vakkari, Ville; Laakso, Lauri
Abstract: The Pandora spectrometer that uses direct‐Sun measurements to derive total column amounts of gases provides an approach for (1) validation of satellite instruments and (2) monitoring of total column (TC) ozone (O3 ) and nitrogen dioxide (NO2 ). We use for the first time Pandora and Ozone Monitoring Instrument (OMI) observations to estimate surface NO2 over marine and terrestrial sites downwind of urban pollution and compared with in situ measurements during campaigns in contrasting regions: (1) the South African Highveld (at Welgegund, 26°34′10″S, 26°56′21″E, 1, 480 m asl, ~120 km southwest of the Johannesburg‐Pretoria megacity) and (2) shipboard U.S. mid‐Atlantic coast during the 2014 Deposition of Atmospheric Nitrogen to Coastal Ecosystems (DANCE) cruise. In both cases, there were no local NO x sources but intermittent regional pollution influences. For TC NO2, OMI and Pandora difference is ~20%, with Pandora higher most times. Surface NO2 values estimated from OMI and Pandora columns are compared to in situ NO2 for both locations. For Welgegund, the planetary boundary layer (PBL) height, used in converting column to surface NO2 value, has been estimated by three methods: co‐located Atmospheric Infrared Sounder (AIRS) observations; a model simulation; and radiosonde data from Irene, 150 km northeast of the site. AIRS PBL heights agree within 10% of radiosonde‐derived values. Absolute differences between Pandora‐ and OMI‐estimated surface NO2 and the in situ data are better at the terrestrial site (~0.5 ppbv and ~1 ppbv or greater, respectively) than under clean marine air conditions, with differences usually >3 ppbv. Cloud cover and PBL variability influence these estimations. Key Points: This analysis estimates surface NO2 from total column Pandora and OMI observations over South Africa and over North Atlantic Ocean Ground and satellite surface NO2 estimations over land are more similar as compared to over ocean with cleaner air Planetary boundary layer height and weather conditions impact the performance of this method in both terrestrial and marine environments